METHODOLOGY AND RESULTS OF PILOT MODEL IDENTIFICATION IN SEMIAUTOMATIC FLIGHT CONTROL - Azarskov, Valerii; Rudyuk, Grygorii (Proceedings of National Aviation University (archive), 2015)
The article reviews statement of identification stage of pilot action models in the control loop, methodology, algorithms and certain results of its performance on flight simulator. New approach is offered for identification of operator dynamic models in moving object control loop. Distinctions are mainly related to multichannel expansion of traditional models that allows considering to a great extent the biological features of the operator.